Compare the Temperature Efficiency of Cabinets Made of Foam and Paper: https://doi.org/10.69692/SUJMRD0901212 - LATHSAATH, Bouapheng; SAIYASAND, Saysamone; SAYSAVANH, Tounta (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
At present, social waste has increased significantly, especially foam and paper wasteLaboratory teaching involves real laboratory equipment so that students are motivated to learn and have real-life experiences from such lessons. Comparison of heat storage efficiency of incubators made of foam and cardboard. There is a purpose To Assess the temperature and humidity passed into foam and cardboard boxes; (2) To Compare the temperature storage efficiency of incubators made of foam and cardboard.The purpose of this experiment was to evaluate the thermal and moisture resistance of foam boxes and paper boxes and to compare the storage efficiency of custom-made incubators using foam boxes and paper boxes.he experiments were performed on 4 levels of temperature and 4 levels of humidity. The experiments were performed on 30 levels of data. The data were analyzed with the Independent Simple T-test at 95% confidence level From the test results of the insulation capacity of the incubator made of foam boxes and paper boxes, it was found that: When the outer surface of the incubator is heated, the temperature of the outer surface changes rapidly, causing heat to begin to accumulate inside the material continuously from the test results of the heat capacity of the incubator made of foam box and paper carton, it was found that: When the outer surface of the incubator is heated, the temperature of the incubator will change rapidly, the heat will start to accumulate inside the material, considering the air temperature in the daytime 28.8, 29.2, 29.5, 33.1 °C the temperature in the test box made of the foam box will change29, 29.4, 29.7, 33.3 °C Respectively the temperature inside the test box made of paper gas will change28.9, 29.3, 29.6, 33.2 °C the time to collect the temperature of both test boxes when testing between temperature changes but It was found that the test box made of paper can hold the temperature in 211,667 seconds and the test box made of foam can record the temperature in 180,997 seconds (P-value<0.05).Incubator made of foam box when the temperature inside the cabinet has an average internal humidity of 48.789%, when the average humidity is 48.012%; the incubator is made of paper gas when the average humidity is 52.515%.and when the temperature inside the temple reached an average relative humidity of 53.737%. (P-value<0.05).